MAPPING OF AGRICULTURAL LANDS IN FLOOD HAZARD AREAS IN HULU SUNGAI TENGAH REGENCY, SOUTH KALIMANTAN - Salamiah, Salamiah; Kumalawati, Rosalina (The Journal is published by Graduate Programe of Lambung Mangkurat University, 2016)
Floods are natural disasters that frequently hit several developed and developing countries including Indonesia every wet season. Floods also occur in agricultural lands. The purpose of this study was to map the agricultural lands in flood hazard areas in Hulu Sungai Tengah Regency, South Kalimantan Province. Data collecting methods used were field research and literature (library research). Data were analyzed using quantitative and qualitative approaches (mixed methods), with the techniques of scoring, SWOT, and spatial analysis (ArcView 3.2 software). Flood hazard levels of most areas in Hulu Sungai Tengah were categorized into no hazard (957.36 km2), low hazard (243.82 km2), medium hazard (455.01 km2), and high hazard (114.91 km2). The use of agricultural lands for rice fields in Hulu Sungai Tengah were located in all subdistricts and flood hazard areas.